Pengaruh Audit Forensik, Audit Investigasi, Kompetensi Auditor, Profesionalisme dan Kecerdasan Spiritual Terhadap Pencegahan Fraud - Ahmad Alfiar Fiar; Jaeni (Universitas Sains dan Teknologi Komputer, 2022)
Forensic audits and investigative audits are used to uncover, detect and prevent fraud. In preventing fraud, the auditor is required to have competence, professionalism and spiritual intelligence to maximize fraud prevention. The population in this study were all auditors who worked at BPKP Representatives of Central Java. The sampling technique used convenience sampling and obtained a sample of 40 respondents. The method of collecting data is through a survey method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that forensic audits, investigative audits, and auditor competence have no significant effect on fraud prevention. while professionalism and spiritual intelligence have a significant positive effect on fraud prevention